DESIGNING VISUAL COMMUNICATION MEDIA AS SUPPORTING CULINARY PROMOTION - Getar Kembara; Fadhli Purnama; Emilia Rosalina (Yayasan Education and Social Center, 2021)
Purwodadi City, Grobogan Regency has many interesting culinary tourism potentials to visit and try the uniqueness of its exotic culinary taste, but the lack of promotional media so that there are very few tourists who come, only at certain times culinary tourist attractions have many visitors. Based on these conditions, the author has the idea to create one of the media that can be used as promotional media, namely brochures, X-banners, and posters, with the hope of encouraging the public to promote culinary tourism in Purwodadi City, Grobogan Regency. The creation of this study project aims to host and develop ideas and ideas about the potential of culinary tourism in Purwodadi in printed visual communication media works in the form of brochures, X-banners, and posters as one of the promotional media for Purwodadi culinary tourism, Grobogan Regency. In his work, the author uses photography techniques combined with computer graphics. The images from the photos are then processed using the Adobe Photoshop and Corel Draw programs to be used as a printed visual communication media design in the form of brochures, X-banners, and posters